High serum clusterin levels are associated with premature coronary artery disease in a Chinese population. Issue 4 (7th February 2019) - Zhu, Huijuan; Liu, Meijuan; Zhai, Tianshu; Pan, Hui; Wang, Linjie; Yang, Hongbo; Yan, Kemin; Gong, Fengying; Zeng, Yong
Abstract: Background: Clusterin plays an important role in the cardiovascular system, and serum levels of clusterin are higher in coronary artery disease patients. Here, we measured serum clusterin levels in premature coronary artery disease (PCAD) patients and explored the association of these levels with PCAD risk. Methods: Serum samples and general clinical information were obtained from 672 subjects including 364 PCAD subjects, 126 non‐PCAD subjects, and 182 controls. Results: Serum clusterin levels were higher in PCAD patients than in controls, particularly in males with body mass index (BMI) < 25 kg/m 2 ( P  < 0.0001). Compared with the lowest tertile of clusterin, the odds ratio of PCAD in the highest tertile was higher in both a univariate and three adjustment models, and it was 3.146‐fold higher in Model 3. This association was especially significant in subgroups with BMI < 25 kg/m 2, total cholesterol < 5.7 mmol/L, high‐density lipoprotein cholesterol ≥ 1.0 mmol/L, Urea < 7.14 mmol/L, and estimated glomerular filtration rate < 90 mL/min/1.73 m 2 . Serum clusterin may be a potential diagnostic biomarker for PCAD (sensitivity 60.7%, specificity 51.6%, area under the curve 0.595 [95% CI, 0.544‐0.647], P  < 0.0001), and a combination of clusterin with clinical variables in Model 3 resulted in improved diagnostic accuracy (sensitivity 86.3%, specificity 64.2%, area under the curve 0.829 [95% CI, 0.782‐0.877], P  < 0.0001). Conclusions: Serum clusterin levels were increased in PCAD patients, especially for males with BMI < 25 kg/m 2 . Higher clusterin levels were independently associated with the presence of PCAD, particularly in subjects with normal BMI, lower total cholesterol, urea, estimated glomerular filtration rate, and higher high‐density lipoprotein cholesterol. Clusterin might be a potential diagnostic biomarker for PCAD patients, especially in combination with clinical variables.